2022
DOI: 10.15678/ier.2022.0801.06
|View full text |Cite
|
Sign up to set email alerts
|

Virtual management during the Covid-19 era: Changes in leadership and management

Abstract: The objective of the article is to understand the impact of the Covid-19 crisis on the management style and the relationship between managers and subordinates. Research Design & Methods:We used a mixed-method combining a qualitative part based on 20 semi-structured interviews as well as a quantitative part based on a questionnaire intended to confirm the observed trends more precisely. All data were analyzed using the grounded theory method. Findings: The analysis of the data shows an irreversible evolution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…They accomplish this through defined skills such as proactivity, opportunity identification, innovation, risk management, and resilience (Branicki et al, 2018;Portuguez Castro et al, 2020). One of the interesting trends which happened when the COVID-19 crisis started, was the major shift in the management style (Montenero & Cazorzi, 2022).…”
Section: Entrepreneurship and Crisismentioning
confidence: 99%
“…They accomplish this through defined skills such as proactivity, opportunity identification, innovation, risk management, and resilience (Branicki et al, 2018;Portuguez Castro et al, 2020). One of the interesting trends which happened when the COVID-19 crisis started, was the major shift in the management style (Montenero & Cazorzi, 2022).…”
Section: Entrepreneurship and Crisismentioning
confidence: 99%
“…Some of them claim that remote work brings many opportunities for organizations. Because of greater control over the time spent on work and family life, the level of employees' concentration increases, and consequently, their satisfaction, sense of emotional attachment to the organization, and organizational commitment also improve (Alshibly et al, 2022;Montenero & Cazorzi, 2022). A study by Bloom et al (2014) indicated that working from home resulted in a 13% increase in employee productivity while also increasing job satisfaction and reducing employee absences and turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is crucial to attract, develop, motivate, and retain employees in organizations. However, remote work popularized during and after COVID-19 created a new approach to leading and managing organizations (Montenero, Cazorzi, 2022).…”
Section: Introductionmentioning
confidence: 99%